Why Does Socialization Matter? : Analyzing the Impact of Socialization and Risk Perception on Energy Saving Behavior - 이창원; 김서용; 최윤희 (Journal of Safety and Crisis Management, 2024)
The purpose of this study is to analyze the determinants of energy saving behavior. This study aims to analyse the factors that influence energy saving behavior with a focus on socialization factors. Social factors are fundamental determinants of energy behavior, but there has been a lack of systematic research on them. According to the results of the survey data, first, the influence of socialization factors is in the order of peer group > parent > experience. In order to strengthen learning in energy conservation in social relationships, it is necessary to use educational communities in the community where peers can exchange experiences. In addition, it is necessary to strengthen parental education to reinforce education at home and to expand the number of experience facilities where people can experience energy conservation. Second, in the risk perception paradigm, perceived benefits > subjective knowledge > trust > perceived risk affect energy conservation in the order of perceived benefits > subjective knowledge > trust > perceived risk. Although these variables have a great influence on energy conservation, these factors are closely related to socialization factors, so strategies to improve perceived risk, benefits, knowledge, and trust using socialization factors are necessary.
Keywords: energy saving behavior; socialization; risk perception